Optical properties of thick, turbid media from picosecond time-resolved light scattering measurements - Brewster, M.Q.; Yamada, Y. (International journal of heat and mass transfer, 1995)
A computational and experimental investigation is reported regarding the feasibility of determining optical properties of turbid media from picosecond (PS) time-resolved light scattering measurements in conjunction with diffusion theory predictions, Monte Carlo simulations, and other appropriate optical measurements. Picosecond time-resolved transmission measurements were performed using aqueous latex particle suspensions with and without absorbing dye. Monte Carlo simulations were also performed to aid in determining limitations of the approach as well as suitable measurement parameters. The system of interest was an optically thick plane-parallel, homogeneous slab consisting of an absorbing, anisotropic scattering medium subject to collimated, pulsed incident radiation. The results of comparing Monte Carlo and diffusion theory predictions showed that important pulse parameters, such as long-time asymptotic log slope and RMS pulse width, are given by diffusion theory analytical expressions with enough accuracy to be useful for determining the unknown optical properties of the medium from time-resolved scattering measurements. These findings were verified using PS time-resolved transmission measurements on aqueous latex particle suspensions. It was also found that the albedo criterion for application of diffusion theory to time-dependent scattering may be much less restrictive than is usually reported (weak absorption or albedo near one is not necessary).